Outlooks of single middle adults on romantic relationships, marriage, and family life - Chua, Camille Joyce L.; Serrano, David P.
This study focuses on the outlooks of single middle adults on romantic relationships, marriage, and family life and their reasons for remaining single. The data was gathered through conducting interview with thirty single middle adults within the age of 45 to 59 years old. It was found that the outlooks of the respondents view romantic relationship as more of a benefit than a cost to the individual and most of them associated it with more positive feelings or approval. The opposite is true for their outlooks on marriage with more of them expressing negative feelings or disapproval towards it as well as espousing the challenges they believe they will face. Meanwhile, their outlooks on family life were focused on parenting and responsibility. They were found to have more positive feelings than negative feelings towards family life. The study classified singlehood into four categories: single by choice, single by constraint, single by choice before becoming a constraint, and single by constraint before becoming a choice. Most of the respondents believe that they were single by choice. The respondents drew their answers from their perceived personal characteristics, personal experiences, and environment.